ICONES ORCHIDACEARUM MALAYENSIUM: ADDIT AMENTA - SMITH, J. J. (REINWARDTIA, 1950)
A few weeks after the publication of the final instalment of the late Dr J. J.Smiths "Icones Orchidacearum Malayensium," volume 2(Bulletin du Jardin Botanique de Buitenzorg, Serie III, Supplement:Volume 3.1949),a dozen more plates of this work were submitted to the Herbarium at Bogor (Buitenzorg) from the authors estate.As inclusion in the aforementioned volume,which was definitely closed last year,appeared undersirable for technical reasons,these addi- tional plates are now issued separately from the"Icones."They still represent an undoubtedly valuable contribution to the correct understand- ing of no less than 54 species of orchids all (except one) previously de- scribed by Dr Smith as new.The explanations were all prepared by the author himself.If the present plates had been incorporated in the main work (which ends with plate 176) in their proper sequence,they would have been numbered 178-189.Of plate 177 only the explanation could be found; the plate itself is missing.The species represented by it are:Liparis arcuata J. J. S., L.endertii J. J. S., L.lycopodioides J. J. S.,and L.biglobulifera J.J. S.